Comparison of antibiotics implanted under the skin and fed in the ration of fattening pigs. - Richardson, D.; Swenson, M.J. (Kansas Agricultural Experiment Station, 2012)
Twenty-five purebred female Poland-China pigs about 10 weeks of age were divided into five lots of five pigs each. The pigs were self-fed in pens having concrete floors. Water barrels with automatic watering cups were used. Since this experiment was conducted during the summer, the pigs were sprayed with water once a day. The basal ration consisted of 72.5 percent milo grain, 15 percent soybean oil meal, 5 percent alfalfa meal, 5 percent tankage, 2 percent steamed bonemeal, and 5 percent salt. All pigs received this ration. The difference in the various treatments was the kind of antibiotic and how it was given to the pigs. A summary of the treatments and the results is given in the accompanying table.
Keywords: Swine; Antibiotic; Feed efficiency; Growth